2011
DOI: 10.1590/s0365-05962011000700019
|View full text |Cite
|
Sign up to set email alerts
|

Hiperqueratose lenticular persistente

Abstract: Flegel's disea se, also known as hyper ke ra to sis len ti cu la ris pers tans, is a rare skin disea se cha racte ri zed by small red dish-brown asympto ma tic hyper ke ra to tic papu les usually loca ted on the lower extremi ties. The his to pa tho lo gi cal fea tu res are hype ror tho ke ra to sis, epi der mal atrophy and band-like inflam matory infil tra te in the super fi cial der mis. Treatment is gene rally inef fec ti ve. We report a case of hyper ke ra tosis len ti cu la ris pers tans that impro ved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It has been suggested that the 5‐FU provokes a strong inflammatory response, leading to the sloughing of the HLP lesion 12,28,35 . However, some works reported a relapse after stopping the therapy 20,36 Topical or systemic retinoids: topical retinoids have not been effective, showing only a slight reduction in roughness 19,20 .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that the 5‐FU provokes a strong inflammatory response, leading to the sloughing of the HLP lesion 12,28,35 . However, some works reported a relapse after stopping the therapy 20,36 Topical or systemic retinoids: topical retinoids have not been effective, showing only a slight reduction in roughness 19,20 .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Ablative treatment (local excision, CO2 laser, curettage, dermabrasion, cryotherapy, and electrocoagulation): these treatments seem to be the most effective because the procedures remove the defective keratinocytes. The absence of recurrence in biopsied areas may prove the efficacy of ablative treatments 36 . However, a large number of lesions, as well as lesion location, makes this an impractical approach.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…It may also be hereditary, with an autosomal dominant transmission. Histologically, the condition is characterized by hyperkeratosis, a thinning or absence of the granular layer, epidermal atrophy, and a band-like infiltrate in the upper dermis [ 42 ]. Waxy keratosis of childhood presents as well-demarcated keratotic papules secondary to abnormal keratinization.…”
Section: Unclassified Disordersmentioning
confidence: 99%